From Alpha to Omicron: anatomy of the SARS-CoV-2 pandemic in an outpatient haemodialysis unit in Johannesburg, South Africa - Maharaj, Ranbir; Dayal, Chandni; Cassimjee, Zaheera; Chiba, Sheetal; Ajayi, Adekunle O; Davies, Malcolm (African Journal of Nephrology, 2023)
Background Recipients of kidney replacement therapy are more susceptible to severe disease and mortality from SARS-CoV-2 infection. We evaluated disease kinetics and clinical outcomes across four COVID-19 outbreak waves in the haemodialysis unit of a tertiary-level hospital in South Africa. Methods Data from 70 patients was analysed. Temporal trends in SARS-CoV-2 infection as diagnosed by nasopharyngeal RT-PCR swab were described as were severity of resultant COVID-19 disease, survival outcomes, and recurrent infections. The effect of patient-related demographic and comorbidity factors, and that of probable SARS-CoV-2 variant on disease severity and recurrence, were additionally assessed. Results Three-quarters of patients in this unit ultimately developed SARS-CoV-2 infection. The majority of infections were asymptomatic or of mild clinical presentation. The Alpha variant (first) wave and the Delta variant (third) wave accounted for the majority of infections. COVID-19 disease was more frequently severe in the Delta variant wave and all mortalities in this cohort occurred in this wave. Male sex and comorbid diabetes were associated with more severe disease. Duration of swab positivity was longer following clinically severe infection and in cases of infection with the Beta variant. Prior episodes of SARS-CoV-2 infection reduced clinical severity at subsequent re-infection and shortened duration of swab positivity. Conclusion The present study is the first description of the COVID-19 pandemic in an African haemodialysis unit. Significant temporal differences in infection rates, disease severity, and survival outcomes were demonstrated over the course of the pandemic in this vulnerable population. Evolving SARS-CoV-2 virulence and immunity potentially account for these differences.